We Trust In Green Product: The Impact Of Green Marketing And Packaging On Purchase Intention - Nila Nailatul Magfiroh; Amelindha Vania (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Customers in Malang City's Generation Z are becoming more conscious of the harm that plastic garbage is doing to the environment. This study investigates the significance of green trust in establishing a connection between the impact of green packaging and marketing and the desire to make green purchases. 170 respondents made up the study's sample and were chosen based on predetermined criteria using a purposive sampling approach. The Partial Least Square (PLS) technique and descriptive statistical analysis were used in the data analysis. The results obtained suggest that green marketing and green packaging have a significant positive effect on green trust. Green trust has a significant positive impact on green purchase intention. Green marketing and green packaging have a significant positive effect on green purchase intention. Green faith acts as a strong mediating factor in the relationship between green marketing and green purchase intention, as well as between green packaging and green purchase intention.